Lectotypification of Dioscorea zingiberensis (Dioscoreaceae), an endemic species from China (Bangladesh Journal of Plant Taxonomy, 2016)
Not available.Bangladesh J. Plant Taxon. 23(1): 87-89, 2016 (June)